Thermal Treatment Impact on Kusia (Nauclea diderrichii) Dimensional Changes - Quartey, Gladys Ama; Marfo, Eric Donkor; Wereko, Emmanuel Yaw; Tetteh, Clara Lily (European Journal of Applied Sciences, 2025)
Thermal treatment of wood has grown significantly in recent decades as a method to enhance wood qualities. Wood is widely used in construction, but its tendency to swell and shrink poses challenges. High-temperature heating reduces these dimensional changes without using chemicals, making it an eco-friendly alternative to chemical modifications. This study examined the effects of thermal treatment on the dimensional stability of Kusia (Nauclea diderrichii) at various temperatures. Results showed that increasing the temperature from 150°C to 240°C improved stability, with anti-shrink efficiency rising from 36.62 to 52.11.